Agreement and differential use of laboratory methods for the detection and quantification of SARS-CoV-2 in experimentally infected animals - Usai, Carla; Pailler-García, Lola; Lorca-Oró, Cristina; Fernández-Bastit, Leira; Roca, Núria; Brustolin, Marco; Rodon, Jordi; Pérez, Mónica; Cantero, Guillermo; Carrillo, Jorge; Izquierdo-Useros, Nuria; Blanco, Julià; et al. (Frontiers in Microbiology, 2022)
Rodents are widely used for the development of COVID-19-like animal models, the virological outcome being determined through several laboratory methods reported in the literature. Our objective was to assess the agreement between methods performed on different sample types from 342 rodents experimentally infected with SARS-CoV-2 (289 golden Syrian hamsters and 53 K18-hACE2 mice). Our results showed moderate agreement between methods detecting active viral replication, and that increasing viral loads determined by either RT-qPCR or infectious viral titration corresponded to increasing immunohistochemical scores. The percentage of agreement between methods decreased over experimental time points, and we observed poor agreement between RT-qPCR results and viral titration from oropharyngeal swabs. In conclusion, RT-qPCR and viral titration on tissue homogenates are the most reliable techniques to determine the presence and replication of SARS-CoV-2 in the early and peak phases of infection, and immunohistochemistry is valuable to evaluate viral distribution patterns in the infected tissues.